2009
DOI: 10.4167/jbv.2009.39.2.103
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Surface Expression of SARS Viral Epitope using Salmonella typhi Cytolysin A

Abstract: The cytolysin A (ClyA) is a 34 kDa pore-forming cytotoxic protein and expressed by some enteric bacteria including Salmonella typhi. This toxin is transported on the bacterial surface and secreted without posttranslational modification. Using the surface display of ClyA, the expression vectors for 193-aa immunogenic antigen of spike protein (termed S1E) from severe acute respiratory syndrome coronavirus (SARS-CoV) were constructed. The vectors carried a gene encoding S. typhi ClyA conjugated to S1E at the C te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The slides were incubated with primary antibody, rabbit anti-ClyA (1:80, distributed by Y.H. 48 ) overnight at 4 °C, followed by incubation with antirabbit immunoglobulin G labeled with biotin (Sigma, St Louis, MO), at room temperature for 80 minutes. Subsequently, streptavidin-horseradish peroxidase (Dako, Glostrup, Denmark) detection system was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The slides were incubated with primary antibody, rabbit anti-ClyA (1:80, distributed by Y.H. 48 ) overnight at 4 °C, followed by incubation with antirabbit immunoglobulin G labeled with biotin (Sigma, St Louis, MO), at room temperature for 80 minutes. Subsequently, streptavidin-horseradish peroxidase (Dako, Glostrup, Denmark) detection system was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Although clyA (34 kDa) was designed to fuse to the antigen, the expression of T. gondii antigens were detected in its clyA‐fusion or nonfusion condition as previously reported (Piao et al . 2009; Huang et al . 2016); the cleavage mechanism of clyA fusion protein remains unknown (Roderer and Glockshuber 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As a limitation of this study, electron microscopy imaging should be included to confirm the presence of OMVs and localization of the antigens. We may link the variation in the clyA-exportation efficiency to the antigen's molecular character, which could alter the conformation of clyA oligomeric assembly (Piao et al 2009). The crystal structure of clyA protein revealed that it has a negatively charged interior, which is cation-selective (Ludwig et al 1999;Willems et al 2017).…”
Section: Growth Rate Of Recombinant S Typhi Vaccine Strainsmentioning
confidence: 99%
“…The expression plasmid pBAD-RLuc8 has been previously described (11). The clyA gene was amplified with 5′-AGTCCATGGTTATGACCGGAATATTTGC-3′ (forward primer) and 5′-GATGTTTAAACTCAGACGTCAGGAACCTC-3′ (reverse primer) using the S. typhi genomic DNA as a template (12). Amplified DNA was cut by NcoI and PmeI and used to directly replace RLuc8 at the same site in pBAD-RLuc8.…”
Section: Methodsmentioning
confidence: 99%